(untitled) (Research, Society and Development, 2021)
Objective: To characterize the microcephaly cases in the west region of Mato Grosso presumably by the congenital Zika virus syndrome. Methods: It is a descriptive study, retrospective in longitudinal design. The study included children with microcephaly presumably by the congenital Zika virus syndrome. The selected variables were the epidemiological profile with sociodemographic data, growth monitoring by the cephalic perimeter evolution, length, weight and body mass index. Results: 12 patients were included in the research. Five children were born with congenital microcephaly and six developed the condition after birth. The cephalic perimeter evolved in an inappropriate way only in the first semester of life, with a growth rate of 0.72 cm/month and being the normal rate 1.5cm/month. The most found complications were tetraparetic cerebral paralysis (91,66%), global delay in neuropsychomotor development (91,66%), epilepsy (58,33%) and pyramidal syndrome (50%). Some findings rarely observed in the literature were found in the research like West syndrome, superior sagittal sinus dilation and single lateral ventricles. All of then presented neuroimaging exam alterations. The most found were pachygyria (66,67%), ventriculomegaly (58,34%) and subcortical calcifications (41,66%). Conclusions: The recognition of the onset phenotype in the congenital Zika virus syndrome will help to ensure an appropriate etiological evaluation and an adequate multi-professional continuous monitoring of these affected children.